Monocytic Myeloid‐Derived Suppressor Cells Accumulate in Renal Transplant Patients and Mediate CD4+Foxp3+ Treg Expansion. Issue 12 (18th September 2013) - Luan, Y.; Mosheir, E.; Menon, M. C.; Wilson, D.; Woytovich, C.; Ochando, J.; Murphy, B.
<x xml:space="preserve">Abstract</x> Myeloid‐derived suppressor cells (MDSC) are negative regulators of the immune response and are in part responsible for the inhibition of the T cell–mediated immune responses. While MDSC have been demonstrated to participate in the induction of prolonged allograft survival in animal models of transplantation, little is known about their immune regulatory function in human transplant recipients. Here, we report that two subsets of human MDSC expressing CD11b+, CD33+ and HLA‐DR− develop in renal patients posttransplantation. We found that CD14+ expressing monocytic MDSC isolated from transplant recipients were highly efficient in suppressing the proliferation of CD4+ T cells in mixed leukocyte reactions. In addition, we observed that CD11b+CD33+HLA‐DR− MDSC are capable of expanding Treg in vitro, and their accumulation overtime after transplantation linearly correlated with an increase in Treg in vivo. This is the first study to link the presence of MDSC with the emergence of Treg in vivo in transplant recipients, and to define the subpopulation of MDSC derived from transplant recipients responsible for generation of Treg. Further studies are necessary to determine the alloimmune regulatory function of MDSC in human transplant recipients.